The effect of different fluid intake on balance performance after recovery with eyes open and eyes closed / Muhammad Syamim Muhamad - Muhamad, Muhammad Syamim (2018)
Drinking fluid during exercise is necessary to prevent performance decreases due to dehydration. The deleterious effects of dehydration on athletic and cognitive performance have been well documented. The effect of dehydration on balance, performance, and proprioception is an important topic in sports. Thus, the aim of this study is to compare the different fluids intake on balance performance after recovery with eyes open and eyes closed. This study were completed by twelve active people (N=l2). Participants balance were measured by Biodex Balance System SD after 20 minutes completed an hour of exercise on treadmill. All participants we go through three different conditions (1: No Fluid; 2: Water Intake; 3: Sport Drink Intake). The results indicate that water and sports drinks were significantly (p < 0.05) improve balance during eyes open. No significant result reported for eyes closed (p > 0.05). The findings identify significant deficits in balance that likely result from decreased proprioceptive and altered posture secondary to dehydration.